Urban resettlement in Xai-Xai, Mozambique after the 2000 floods: implications for the living conditions of households engaged in agriculture - Chambule, Hilartino Lucas (My University, 2012)
This study takes a case study approach and its study area consists of two settlements, namely Xai-Xai Riverbank and Ndambine. The data collected and analyzed in this study was quantitative and qualitative in nature. This is an assessment study in that it assesses the impact of involuntary emergency resettlement on the living conditions of people engaged in agriculture. Research methods used to gather data in this study were literature review (including grey literature review), surveys (questionnaires and interviews), and non-participant observations. Forty residents of Ndambine formed part of the respondents that took part in this study. The findings of the study show that involuntary emergency resettlement impacts on the affected people both negatively and positively. In other words, there are both advantages and disadvantages to different people. However, in the case of the resettled people of Ndambine, the findings of the study seem to suggest that the living conditions of the majority of the resettled people engaged in agriculture are better in Ndambine settlement than they were in Xai-Xai Riverbank settlement. The key challenge for the government of Mozambique is to improve on its disaster management and mitigation strategies in order to ensure that resettlements caused by floods are as undisruptive as possible and losses suffered by the affected people are minimized.